2020
DOI: 10.1590/0034-7167-2019-0471
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for site complications of intravenous therapy in children and adolescents with cancer

Abstract: ABSTRACT Objectives: to analyze predictive factors for the incidence of complications related to peripheral venous catheters in children and adolescents with cancer. Methods: a longitudinal follow-up study, conducted at a pediatric oncology clinic unit of a hospital in Bahia, with 333 peripheral venous catheters inserted in 77 children and 26 adolescents. Data collection took place between April 2015 and December 2016 through direct observation of peripheral intravenous catheter insertion, medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…This alarmingly high incidence is approximately 2.5 times higher than the 34% found in a recent systematic review and meta-analysis of 32 studies [1]) . Similarly, the incidence of complications per PIVC inserted was higher (67%) compared with other studies on paediatric populations which reported incidences of 16% -51.9% [12][13][14] ~ 7 ~ Infiltration of the skin or subcutaneous tissue with intravenous fluid or drugs comprised 60% of the clinical complications, higher than the 10% to 33% found in other studies [7,8,12,13] . Phlebitis was the second most common clinical complication with an incidence of 29%.…”
Section: Discussionmentioning
confidence: 61%
“…This alarmingly high incidence is approximately 2.5 times higher than the 34% found in a recent systematic review and meta-analysis of 32 studies [1]) . Similarly, the incidence of complications per PIVC inserted was higher (67%) compared with other studies on paediatric populations which reported incidences of 16% -51.9% [12][13][14] ~ 7 ~ Infiltration of the skin or subcutaneous tissue with intravenous fluid or drugs comprised 60% of the clinical complications, higher than the 10% to 33% found in other studies [7,8,12,13] . Phlebitis was the second most common clinical complication with an incidence of 29%.…”
Section: Discussionmentioning
confidence: 61%
“…A meta-analysis of adult patients reported an incidence rate of 31% [8]. However, in the pediatric population, percentages ranged from 5% to 53.4% owing to differences in the definition of phlebitis and in the type of patients included [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A PIC can trigger negative reactions in children, such as refusal of the procedure, crying, muscle tension and contracted posture (1) to this procedure, contributing to the child's and family's discomfort. Also, the use of peripheral IVT in children can cause complications, with a frequency that varies from 18.6 to 55.6% (2)(3)(4)(5)(6) , such as bruises, phlebitis/thrombophlebitis, infiltration/leakage, local infection, nerve damage, vessel spasms (7) and catheter obstruction. When these complications occur, the intravenous catheter is removed, and a new PIC is required.…”
Section: Introductionmentioning
confidence: 99%